Insulated soft magnetic metal powder and dust core

By using an insulating coated soft magnetic metal powder with a specific oxide layer composition and controlled diffusion layer thickness, the issue of loss reduction in insulating coated soft magnetic metal powders is addressed, resulting in improved magnetic properties.

JP7649209B2Active Publication Date: 2025-03-19NITERRA CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021113356
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-08
Publication Date
2025-03-19
Estimated Expiration
2041-07-08

AI Technical Summary

Technical Problem

Existing insulating coated soft magnetic metal powders face issues with losses due to diffusion of insulating layer components into the soft magnetic metal, negatively affecting their properties.

Method used

The development of an insulating coated soft magnetic metal powder with soft magnetic metal particles coated with an oxide layer of Al or Zr, where the half-value width of the strongest peak from the insulating layer is below 0.80° and the diffusion layer thickness is 50 nm or less.

Benefits of technology

This solution effectively reduces losses in insulating coated soft magnetic metal powders by minimizing the diffusion of insulating layer components and enhancing the crystallinity of the oxide layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649209000002
    Figure 0007649209000002
  • Figure 0007649209000003
    Figure 0007649209000003
  • Figure 0007649209000004
    Figure 0007649209000004
Patent Text Reader

Abstract

To decrease the loss of insulation coating soft-magnetic metal powder.SOLUTION: The insulation coating soft-magnetic metal powder 1 hereof comprises: soft-magnetic metal particles 2 having an average equivalent circle diameter of 10-100 μm; and an insulation layer 3 formed on a surface of each soft-magnetic metal particle 2. In the insulation coating soft-magnetic metal powder 1, the insulation layer 3 contains oxide of at least one element of Al and Zr. A half-peak width of a strongest peak coming from the insulation layer 3, measured by XRD is equal to or smaller than 0.80°. A diffusion layer 5A, 5B resulting from diffusion of the element in a surface layer of the soft-magnetic metal particle 2 is 50 nm or smaller in thickness.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an insulating coated soft magnetic metal powder and a powder core. [Background technology]

[0002] Patent Document 1 discloses a soft magnetic metal powder having particles each composed of a soft magnetic metal portion and a coating portion that covers the soft magnetic metal portion. The coating portion contains an oxide of Si, and has a first coating portion containing amorphous matter and a second coating portion containing crystals.

[0003] Patent Documents 2 and 3 describe insulating coated soft magnetic metal powders using zirconium oxide. Patent Document 4 describes soft magnetic powders having an oxygen value per unit specific surface area within a predetermined range. Patent Document 5 describes a dust core using particles in which an insulating coating of metal oxide is formed on the surface of metal magnetic particles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-167384 A [Patent Document 2] Japanese Patent Application Publication No. 10-335128 [Patent Document 3] JP 2019-192868 A [Patent Document 4] JP 2020-186414 A [Patent Document 5] JP 2009-164401 A Summary of the Invention [Problem to be solved by the invention]

[0005] In insulating-coated soft magnetic metal powder, soft magnetic metal particles are coated with an insulating layer to reduce loss, but the components of the insulating layer tend to diffuse into the soft magnetic metal, adversely affecting the properties of the soft magnetic metal particles. The present disclosure has been made in view of the above-mentioned circumstances, and has an object to reduce loss in an insulating coated soft magnetic metal powder. The present disclosure can be realized in the following forms. [Means for solving the problem]

[0006] [1] An insulating-coated soft magnetic metal powder comprising soft magnetic metal particles having an average equivalent circular diameter of 10 μm to 100 μm and an insulating layer formed on the surface of the soft magnetic metal particles, The insulating layer contains an oxide of at least one of Al and Zr, the half-value width of the strongest peak derived from the insulating layer as measured by XRD is 0.80° or less; The insulating coated soft magnetic metal powder has a diffusion layer in which the element is diffused on the surface of the soft magnetic metal particle, the diffusion layer having a thickness of 50 nm or less. Effect of the Invention

[0007] According to the present disclosure, loss in the insulating coated soft magnetic metal powder can be reduced. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a cross-sectional view that typically illustrates a cross section of a powder magnetic core. [Diagram 2] FIG. 2 is a schematic diagram of a thin sample. [Diagram 3] 1 is a graph showing a schematic diagram of Zr concentration when the thickness of a diffusion layer is 50 nm or less. [Figure 4] 1 is a schematic graph of the Zr concentration when the thickness of the diffusion layer is greater than 50 nm. [Diagram 5] FIG. 13 is a graph showing the Zr concentration in the powder magnetic core of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Here, a preferred example of the present disclosure is given. [2] An insulated coated soft magnetic metal powder, in which particles having an equivalent circle diameter of 50 μm to 100 μm are defined as specific particles among the soft magnetic metal particles, and when cross sections of 10 or more different specific particles are subjected to crystal orientation analysis and the number of regions separated by an orientation difference of 5° or more is counted for each of the specific particles, the average number of the regions counted for each of the specific particles is 9 or less.

[0010] [3] A dust core comprising an insulating coated soft magnetic metal powder.

[0011] [4] A powder magnetic core, in which, when a cross section of the powder magnetic core is observed in a field of view of 500 μm × 500 μm, the proportion of the area occupied by the insulating layer is 4% or more and 9% or less when the area of ​​the entire powder magnetic core is taken as 100%.

[0012] [5] When a cross section of the powder magnetic core is observed in ten consecutive fields of view of 100 μm × 100 μm, the ratio of the area occupied by pores to the area of ​​the fields of view is 5% or less; A powder magnetic core, wherein the proportion of an area occupied by pores present between the soft magnetic metal particles and the insulating layer is 20% or less when the total area occupied by the pores is taken as 100%.

[0013] The present disclosure will be described in detail below. In this specification, a description using "~" for a numerical range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".

[0014] 1. Insulating coated soft magnetic metal powder 1 The insulating coated soft magnetic metal powder 1 includes soft magnetic metal particles 2 having an average equivalent circle diameter of 10 μm to 100 μm, and an insulating layer 3 formed on the surface of the soft magnetic metal particle 2. The insulating layer 3 contains an oxide of at least one of Al and Zr. The half width of the strongest peak derived from the insulating layer 3 measured by XRD is 0.80° or less. The thickness of the diffusion layers 5A and 5B in which elements are diffused in the surface layer of the soft magnetic metal particle 2 is 50 nm or less.

[0015] (1) Soft magnetic metal particles 2 The soft magnetic metal particles 2 are not particularly limited as long as they are soft magnetic metal particles, and can be widely used. As the soft magnetic metal particles 2, soft magnetic pure iron particles and iron-based alloy particles can be widely used. As the iron-based alloy, Fe-Si alloy, Fe-Si-Cr alloy, Fe-Si-Al alloy (Sendust), Ni-Fe alloy (Permalloy), Ni-Fe-Mo alloy (Supermalloy), Fe-based amorphous alloy, Fe-Co alloy, etc. can be suitably used. Among these, Fe-Si alloy, Fe-Si-Cr alloy, Fe-Si-Al alloy (Sendust), Ni-Fe alloy (Permalloy), Ni-Fe-Mo alloy (Supermalloy) are preferable from the viewpoint of magnetic permeability, coercive force, and frequency characteristics. When an Fe—Si alloy is used, for example, an alloy having a composition of 0.1 mass % to 10 mass % Si, the balance being Fe and unavoidable impurities can be used. When using an Fe-Si-Cr alloy, for example, an alloy having a composition of Si: 0.1 mass % to 10 mass %, Cr: 10 mass % to 20 mass %, and the remainder: Fe and unavoidable impurities can be used. The average equivalent circular diameter of the soft magnetic metal particles 2 is 10 μm or more and 100 μm or less, preferably 25 μm or more and 100 μm or less, and more preferably 50 μm or more and 100 μm or less. The average equivalent circular diameter of the soft magnetic metal particles 2 can be appropriately changed depending on the frequency band to be used. In particular, when assuming use in a high frequency band exceeding 100 kHz, it is more preferable that the average equivalent circular diameter is 10 μm or more and 25 μm or less. The average equivalent circle diameter of the soft magnetic metal particles 2 can be obtained by forming a dust core 10 containing the insulating coated soft magnetic metal powder 1 and observing the cross section of the dust core 10 (see FIG. 1). Specifically, the average equivalent circle diameter is calculated from the particle area observed by FE-SEM on the cross section of the dust core 10. More specifically, the average equivalent circle diameter is obtained as follows. Focus is placed on a plurality of soft magnetic metal particles 2 that can be observed without chipping in a predetermined observation field (e.g., 200 μm×200 μm). The diameter (equivalent circle diameter) of an ideal circle (true circle) having an area equal to the area (projected area) of each particle image of the soft magnetic metal particles 2 is calculated as the equivalent circle diameter of each particle. The average equivalent circle diameter is then obtained by arithmetically averaging the equivalent circle diameters of each particle. The equivalent circle diameter of each particle and the average equivalent circle diameter can be obtained using general image analysis software.

[0016] (2) Insulating layer 3 As described above, the insulating layer 3 contains an oxide of at least one of the elements Al and Zr (hereinafter also referred to as the specific element). The insulating layer 3 may contain an oxide of Si in addition to the oxide of the specific element. Examples of oxides of Al (aluminum) include γ-Al2O3 and α-Al2O3. Examples of oxides of Zr (zirconium) include monoclinic ZrO2, tetragonal ZrO2, and cubic ZrO2. Examples of oxides of Si (silicon) include quartz and cristobalite. The oxide may be a composite oxide containing a specific element, or a mixture of the above oxides. Examples of such composite oxides include MgO-Al2O3 composite oxide, Y2O3-ZrO2 composite oxide, CaO-ZrO2 composite oxide, etc. Examples of such mixtures include ZrO2-SiO2 mixture, Al2O3-SiO2 mixture, ZrO2-Al2O3 mixture, Al2O3-SiO2-MgO mixture, etc. When a ZrO2-SiO2 mixture is used, for example, a mixture of SiO2: 1 mass % to 45 mass %, the remainder: ZrO2 and unavoidable impurities can be used. When an Al2O3-SiO2 mixture is used, for example, a mixture of SiO2: 1 mass % to 45 mass %, the remainder: Al2O3 and unavoidable impurities can be used. When a ZrO2-Al2O3 mixture is used, for example, a mixture of Al2O3: 1 mass % to 30 mass %, the remainder: ZrO2 and unavoidable impurities can be used. When an Al2O3-SiO2-MgO mixture is used, for example, a mixture of SiO2: 1 mass % to 45 mass %, MgO: 1 mass % to 10 mass %, and the remainder: Al2O3 and unavoidable impurities can be used. The composition of the insulating layer 3 can be analyzed by an EPMA (Electron Probe Micro Analyser).

[0017] When the insulating layer 3 is observed with a TEM (transmission electron microscope), particles that make up the insulating layer 3 are confirmed. At least a part of these particles is formed by crystals of the above-mentioned oxide. There is no particular limitation on the average equivalent circle diameter of the particles constituting the insulating layer 3. From the viewpoint of suppressing eddy current loss, the average equivalent circle diameter of the particles constituting the insulating layer 3 is preferably 20 nm to 50 nm. The average equivalent circle diameter of the particles constituting the insulating layer 3 can be obtained by forming a dust core 10 containing the insulating coated soft magnetic metal powder 1 and observing the cross section of the dust core 10. Specifically, the average equivalent circle diameter is calculated from the particle area observed by TEM on the cross section of the dust core 10. More specifically, the average equivalent circle diameter is obtained as follows. Focus is placed on a plurality of particles that can be observed without missing particles in five 300 nm × 300 nm square observation fields. The diameter (equivalent circle diameter) of an ideal circle (true circle) having an area equal to the area (projected area) of each particle image is calculated as the equivalent circle diameter of each particle. The average equivalent circle diameter is then obtained by arithmetically averaging the equivalent circle diameters of each particle. The equivalent circle diameter of each particle and the average equivalent circle diameter can be obtained using general image analysis software.

[0018] (3) Requirement for the half-width of the strongest peak originating from the insulating layer 3 In the insulating coated soft magnetic metal powder 1, the half width of the strongest peak derived from the insulating layer 3 measured by XRD is 0.80° or less. The half width of the strongest peak derived from the insulating layer 3 being equal to or less than a predetermined value can be an indicator of high crystallinity of the oxide contained in the insulating layer 3. The half width of the strongest peak may be equal to or less than 0.72°, or may be equal to or less than 0.66°. The lower limit of the half width of the strongest peak is not particularly limited, but is usually equal to or more than 0.40°. The half-value width of the strongest peak derived from the insulating layer 3 can be controlled by adjusting the composition of the insulating layer 3 and the heat treatment conditions in the manufacturing method described later.

[0019] The half-value width of the strongest peak derived from the insulating layer 3 can be determined by XRD measurement of the dust core 10 containing the insulating-coated soft magnetic metal powder 1. The XRD measurement is performed, for example, under the following conditions. Equipment: Rigaku SmartLab X-ray: CuKα1 Tube voltage: 40kV ·Tube current: 30mA Scanning speed: 5° / min Sampling width: 0.02° Measurement range (2θ): 10°~80° Entrance slit: 1 / 2° Receiving slit 1: 15.000mm Receiving slit 2: 20.000mm In the diffraction pattern of the powder core 10 obtained by XRD measurement, peaks originating from the soft magnetic metal particles 2, the measurement cell, etc. are excluded, and only peaks originating from the insulating layer 3 are obtained. When there is one peak originating from the insulating layer 3, that peak is identified as the strongest peak. When there are multiple peaks originating from the insulating layer 3, the peak with the highest intensity among the multiple peaks is identified as the strongest peak. For example, when two types of peaks, monoclinic ZrO2 and tetragonal ZrO2, are detected in an insulating layer 3 containing ZrO2, only the peak with the higher intensity (e.g., tetragonal ZrO2) is identified as the strongest peak.

[0020] Examples of the crystal phase exhibiting the strongest peak derived from the insulating layer 3 include crystal phases selected from the group consisting of monoclinic ZrO2, tetragonal ZrO2, cubic ZrO2, γ-Al2O3, and SiO2 (quartz). Examples of the strongest peaks in these crystal phases are as follows. Among these, the strongest peak is preferably any one of the peaks of monoclinic ZrO2, tetragonal ZrO2, cubic ZrO2, or γ-Al2O3. Monoclinic ZrO2 PDF card number: 01-080-0966 Strongest peak (hkl): (-1,1,1) d value of strongest peak: 3.15 Tetragonal ZrO2 PDF card number: 01-073-1441 Strongest peak (hkl):(0,1,1) d value of strongest peak: 3.00 ·Cubic ZrO2 PDF card number: 01-080-4012 Strongest peak (hkl):(1,1,1) d value of strongest peak: 2.97 γ-Al2O3 PDF card number: 00-010-0173 Strongest peak (hkl):(4,4,0) d value of strongest peak: 1.40 ·SiO2 (quartz) PDF card number: 00-033-1161 Strongest peak (hkl):(1,0,1) d value of strongest peak: 3.34

[0021] (4) Requirements for the thickness of the diffusion layers 5A and 5B The thickness of the diffusion layers 5A and 5B in which the specific elements (Al, Zr) are diffused in the surface layer of the soft magnetic metal particles 2 is 50 nm or less. The diffusion layers 5A, 5B can be generated by diffusing a specific element into the soft magnetic metal particles 2 by heat treatment or the like. That is, the diffusion layers 5A, 5B can be generated in the area where the soft magnetic metal particles 2 and the insulating layer 3 are in close contact with each other. The diffusion layers 5A, 5B may be formed on the entire surface layer of the soft magnetic metal particles 2, or may be formed partially on the surface layer of the soft magnetic metal particles 2. The diffusion layers 5A, 5B may not be formed (their thickness may be 0 nm). The thickness of the diffusion layers 5A and 5B can be controlled by adjusting the rate of temperature rise within a predetermined temperature range in the manufacturing method described below.

[0022] Whether the thickness of the diffusion layers 5A, 5B is 50 nm or less is determined by TEM-EDS (energy dispersive X-ray spectrometry) measurement of the powder core 10 containing the insulating coated soft magnetic metal powder 1. Specifically, the powder core 10 is processed into a thin sample 11 having a thickness of 100 nm by a FIB (focused ion beam) device, and a TEM-EDS measurement is performed. The TEM-EDS measurement is performed under conditions equivalent to a predetermined resolution (e.g., Φ10 nm). An example of such measurement conditions is a beam diameter of Φ0.24 nm, an acceleration voltage of 200 keV, and an irradiation current of 30 μA.

[0023] The thin sample 11 will be described. As shown in FIG. 2, the thin sample 11 is processed so that a cross section of the insulating layer 3 appears on the FIB observation surface S1 and the TEM observation surface S2. The TEM observation surface S2 of the thin sample 11 is the XY surface, and the FIB observation surface S1 is the XZ surface. The boundary between the insulating layer 3 and the soft magnetic metal particles 2A and 2B appears on the FIB observation surface S1. The inclination of both boundary lines is 100 nm vertically (Z-axis direction) and 10 nm horizontally (X-axis direction) or less. FIG. 2 shows that the inclination of the boundary line on the right side is within a predetermined range, but the inclination of the boundary line on the left side is also within a predetermined range. The TEM-EDS observation is performed on the TEM observation surface S2 at a position 600 nm from the FIB observation surface S1. In this way, it is possible to suppress the insulating layer 3 components present inside the thin sample 11 from being detected as the diffusion layers 5A and 5B due to the inclination of the insulating layer 3 with respect to the Z-axis. In FIG. 2, the diffusion layers 5A and 5B are omitted.

[0024] When the element contained in the insulating layer 3 is Zr, whether the diffusion layers 5A, 5B are 50 nm or less is determined by the following procedure, which will be described below with reference to FIGS. [1] A TEM observation image is obtained on the TEM observation surface S2, and a line analysis is performed on the measurement line ML that crosses the insulating layer 3 at a position 600 nm from the FIB observation surface S1. [2] Two lines L1 and L2 are drawn perpendicular to the measurement line ML from the intersection of the measurement line ML and the boundary between the soft magnetic metal particles 2A and 2B and the insulating layer 3. Line L1 is located on the left side of the insulating layer 3, and line L2 is located on the right side of the insulating layer 3. [3] Calculate the average value of all points of Zr concentration obtained by linear analysis in the measurement range inside the two lines L1 and L2. This average value is defined as the 100% line of Zr concentration. [4] Calculate the average value of all points of Zr concentration obtained by line analysis in the measurement range from 500 nm to the left of line L1 and from 500 nm to the right of line L2. This average value is defined as the base (0%) line of Zr concentration. [5] Calculate the 10% line of Zr concentration based on the base (0%) line of Zr concentration and the 100% line of Zr concentration. Find points P1 and P2 that are the outermost points where the 10% line of Zr concentration intersects with the Zr concentration graph. [6] Calculate the distance between point P1 and line L1. From the TEM observation image, determine the angle θ1 (0°<θ1≦90°) between the boundary line between the soft magnetic metal particle 2A and the insulating layer 3 and the measurement line ML. Calculate the thickness T1 of the diffusion layer 5A based on the following formula. Thickness T1 of the diffusion layer 5A = distance between point P1 and line L1 × sin θ1 The distance between point P2 and line L2 is calculated. From the TEM observation image, the angle θ2 (0°<θ2≦90°) between the boundary line between the soft magnetic metal particle 2B and the insulating layer 3 and the measurement line ML is obtained. The thickness T2 of the diffusion layer 5B is calculated based on the following formula. Thickness T2 of the diffusion layer 5B = distance between point P2 and line L2 × sinθ2 [7] When the thickness T1 of the diffusion layer 5A is 50 nm or less and the thickness T2 of the diffusion layer 5B is 50 nm or less, it is judged that the "thickness of the diffusion layer is 50 nm or less" (see FIG. 3). When at least one of the thickness T1 of the diffusion layer 5A and the thickness T2 of the diffusion layer 5B is greater than 50 nm, it is judged that the "thickness of the diffusion layer is greater than 50 nm" (see FIG. 4). The thicknesses T1 and T2 of the diffusion layers 5A and 5B may be 0 nm, that is, the diffusion layers 5A and 5B may not be detected.

[0025] The insulating coated soft magnetic metal powder 1 may be determined to have a "diffusion layer thickness of 50 nm or less" by line analysis at one location on at least one soft magnetic metal particle 2. The insulating coated soft magnetic metal powder 1 is preferably determined to have a "diffusion layer thickness of 50 nm or less" by line analysis at three different locations on one soft magnetic metal particle 2. Moreover, the insulating coated soft magnetic metal powder 1 is more preferably determined to have a "diffusion layer thickness of 50 nm or less" by line analysis of multiple flake samples 11 obtained from different positions on the powder core 10. The number of multiple flake samples 11 is preferably 3 or more, more preferably 5 or more, and even more preferably 10 or more.

[0026] When the element contained in the insulating layer 3 is Al, the Al concentration can be measured and the judgment can be made in a similar manner. When the insulating layer 3 contains both Al and Zr, it is sufficient to confirm that all elements meet the requirements. Even when the insulating film contains an oxide of an element other than Al and Zr (e.g., an oxide of Si), the thickness of the diffusion layer is defined by the Zr concentration or Al concentration, and the concentrations of elements other than Al and Zr are not taken into consideration.

[0027] (5) Presumed reason for loss suppression of insulated soft magnetic metal powder 1 (dust core 10) The present inventors have conducted extensive research to suppress the loss (iron loss) of the insulated soft magnetic metal powder 1 (dust core 10). As a result, they have found that the desired effect can be achieved in the dust core 10 obtained by controlling the processing conditions during heat treatment when the following requirements are satisfied. That is, they have unexpectedly discovered that the loss of the dust core 10 can be suppressed when the half-width of the strongest peak derived from the insulating layer 3 measured by XRD is 0.80° or less and the thickness of the diffusion layer 5A, 5B in which at least one element of Al or Zr is diffused in the surface layer of the soft magnetic metal particle 2 is 50 nm or less. The present invention has been made based on this finding. The same effect as that of the dust core 10 is also confirmed in the insulated soft magnetic metal powder 1. Although it is not clear why the desired effect is obtained in this embodiment, it is presumed as follows. It is presumed that if the half-width of the strongest peak derived from the insulating layer 3 measured by XRD is 0.80° or less, oxide crystals with a predetermined crystallinity are generated in the insulating layer 3, resulting in reduced loss. Furthermore, if the thickness of the diffusion layers 5A, 5B in which at least one element of Al or Zr is diffused in the surface layer of the soft magnetic metal particle 2 is 50 nm or less, the effect of Al or Zr on the soft magnetic metal particle 2 is suppressed, and thus the loss is reduced.

[0028] (6) Crystal orientation requirements In the insulating coated soft magnetic metal powder 1, when specific particles are those having a circle equivalent diameter of 50 μm to 100 μm among the soft magnetic metal particles 2, and cross sections of 10 or more different specific particles are subjected to crystal orientation analysis to count the number of regions separated by an orientation difference of 5° or more for each specific particle, it is preferable that the average number of regions counted for each specific particle is 9 or less. The average number of regions counted for the specific particles is preferably 8 or less, and more preferably 7 or less. The average number of regions measured in a specific particle can be an index representing the degree of crystal division in a soft magnetic metal particle. If the average number of regions measured in a specific particle is equal to or less than a predetermined value, an increase in hysteresis loss is suppressed, and the loss is reduced accordingly. The lower limit of the average number of regions measured in a specific particle may be 1 or more, and is usually 2 or more. The number of regions in a specific particle can be determined by electron backscatter diffraction (EBSD) measurement. EBSD measurement is performed, for example, under the following conditions. Acceleration voltage: 10.00kV Specimen tilt (degrees): 70.00° Acquisition rate: 109.15Hz Based on the crystal orientation map obtained by EBSD measurement, measurement points with an orientation difference of 5° or more between adjacent measurement points are defined as grain boundaries, and the number of areas surrounded by grain boundaries is counted. However, among the areas surrounded by grain boundaries, areas with an equivalent circle diameter of 3 μm or less are excluded from the count. Areas with an equivalent circle diameter of 3 μm or less are excluded from the count in order to eliminate errors in EBSD measurement caused by noise, etc.

[0029] 2.Powder magnetic core 10 The above-mentioned insulating coated soft magnetic metal powder 1 is useful as a material for a powder magnetic core. That is, the powder magnetic core 10 preferably contains the insulating coated soft magnetic metal powder 1. In addition, in the description of the powder magnetic core 10, the description of the above-mentioned insulating coated soft magnetic metal powder 1 is referred to for similar points.

[0030] (1) Requirements regarding the proportion of the area occupied by the insulating layer When the cross section of powder core 10 is observed in a field of view of 500 μm × 500 μm, the area of ​​insulating layer 3 is preferably 4% or more and 9% or less when the area of ​​the entire powder core 10 is taken as 100%. The area ratio of insulating layer 3 is more preferably 5% or more and 7% or less. As long as the area ratio of insulating layer 3 is within a predetermined range, a good balance between hysteresis loss and eddy current loss is achieved. In other words, if the area ratio of insulating layer 3 is too high, hysteresis loss will be large, and if it is too low, eddy current loss will be large. The ratio of the area occupied by the insulating layer 3 can be calculated by observing a cross section processed by a CP (cross section polisher) with an EPMA and analyzing the image. Note that the area occupied by the insulating layer 3 does not include the area of ​​the pores 6. The proportion of the area occupied by the insulating layer 3 can be controlled by adjusting the mixing ratio of the raw material of the soft magnetic metal particles 2 and the raw material of the insulating layer 3.

[0031] (2) Requirements for pores 6 From the viewpoint of further reducing eddy current loss, it is more preferable that the powder magnetic core 10 satisfies the following requirements regarding the pores 6. When the cross section of the powder core 10 is observed in 10 continuous fields of view of 100 μm × 100 μm, it is preferable that the ratio of the area occupied by the pores 6 to the area of ​​the fields of view is 5% or less, and when the total area occupied by the pores 6 is taken as 100%, the ratio of the area occupied by the pores 6A present between the soft magnetic metal particles 2 and the insulating layer 3 is 20% or less. In Fig. 1, of the pores 6, the pores 6 present between the soft magnetic metal particles 2 and the insulating layer 3 are distinguished as pores 6A. The ratio of the area occupied by the pores 6 to the area of ​​the field of view is more preferably 4.5% or less, and further preferably 4% or less. The ratio of the area occupied by the pores 6 to the area of ​​the field of view is usually 1% or more. When the total area occupied by the pores 6 is taken as 100%, the area ratio occupied by the pores 6A present between the soft magnetic metal particles 2 and the insulating layer 3 is more preferably 18% or less, and further preferably 16% or less. The area ratio occupied by the pores 6A present between the soft magnetic metal particles 2 and the insulating layer 3 is usually 6% or more. The area occupied by the pores 6 and the ratio of the area occupied by the pores 6A present between the soft magnetic metal particles 2 and the insulating layer 3 can be calculated by clarifying the pores 6 using a backscattered electron image of an FE-SEM and performing image analysis. This requirement can be controlled by adjusting the pressing pressure when press-molding the powder core 10 and the concentration of the oxide particles in the suspension in the manufacturing method described below. Increasing the concentration of the oxide particles in the suspension increases the proportion of the area occupied by the pores 6A, and decreasing the concentration decreases the proportion of the area occupied by the pores 6A.

[0032] (3) Requirement for difference between the thermal expansion coefficient of the soft magnetic metal particles 2 and the thermal expansion coefficient of the insulating layer 3 In the powder magnetic core 10, the difference between the thermal expansion coefficient of the soft magnetic metal particles 2 and the thermal expansion coefficient of the insulating layer 3 is 3.0×10 -6 The difference between the thermal expansion coefficient of the soft magnetic metal particles 2 and the thermal expansion coefficient of the insulating layer 3 is preferably 2.8×10 -6 / K or less, and more preferably 2.5×10 -6 / K or less. If the difference between the thermal expansion coefficient of the soft magnetic metal particles 2 and the thermal expansion coefficient of the insulating layer 3 is a predetermined value or less, it is possible to reduce the performance degradation after thermal cycling assuming an actual usage environment. The difference between the thermal expansion coefficient of the soft magnetic metal particles 2 and the thermal expansion coefficient of the insulating layer 3 is expressed as an absolute value and is 0 or more.

[0033] The difference between the thermal expansion coefficient of the soft magnetic metal particles 2 and the thermal expansion coefficient of the insulating layer 3 can be found as follows. The soft magnetic metal particles 2 are press molded without being coated with an insulating layer to prepare individual samples of the soft magnetic metal particles 2. If individual powder of the soft magnetic metal particles 2 is not available, the composition of the soft magnetic metal alone is found from a sample of the insulating-coated soft magnetic metal powder 1, and an individual sample of this composition is prepared. Soft magnetic metal particles 2 are coated with an insulating layer 3 and press-molded to prepare a dust core 10. The thermal expansion amounts of a single sample of soft magnetic metal particles 2 and powder core 10 are measured in the range of 25° C. to 100° C. in accordance with JIS R 1618. The thermal expansion amount measured for the single sample is designated A, and the thermal expansion amount measured for powder core 10 is designated B. The rate of change in A relative to temperature change in the range of 25° C. to 100° C. is calculated as the thermal expansion coefficient of the soft magnetic metal particles 2. The value obtained by the following formula (1) is regarded as the amount of thermal expansion C of the insulating layer 3. C=BA (1) The rate of change in C relative to temperature changes in the range of 25° C. to 100° C. is calculated as the thermal expansion coefficient of insulating layer 3. From the calculated thermal expansion coefficients of the soft magnetic metal particles 2 and the insulating layer 3, the difference between the thermal expansion coefficients of the soft magnetic metal particles 2 and the insulating layer 3 is determined. The thermal expansion coefficients of the soft magnetic metal particles 2 and the insulating layer 3 can be controlled by appropriately designing the combination of the composition of the soft magnetic metal particles 2 and the composition of the insulating layer 3.

[0034] The combination of the composition of the soft magnetic metal particles 2 and the composition of the insulating layer 3 is not particularly limited. From the viewpoint of reducing the difference in thermal expansion coefficient, the preferred combination of the composition of the soft magnetic metal particles 2 and the composition of the insulating layer 3 is as follows: In addition, the combinations of the composition of the soft magnetic metal particles and the composition of the insulating layer described in Examples 18 to 19 can also be used. A combination in which the soft magnetic metal particles 2 are Fe-3.0 mass % Si and the insulating layer 3 is ZrO2 A combination of the soft magnetic metal particles 2 being Fe-6.5 mass% Si and the insulating layer 3 being Al2O3-20 mass% SiO2-5 mass% MgO. A combination in which the soft magnetic metal particles 2 are pure iron (100% Fe) and the insulating layer 3 is ZrO2

[0035] 3. Method for producing the insulating coated soft magnetic metal powder 1 and the dust core 10 There is no particular limitation on the method for producing the insulating coated soft magnetic metal powder 1 and the dust core 10. An example will be described below. (1) Preparation of insulated soft magnetic metal powder 1 A suspension containing soft magnetic metal powder, oxide particles of a specific element, and a small amount of organic components is mixed and dried. The obtained dried powder is heat-treated to obtain the insulating coated soft magnetic metal powder 1. The conditions of this heat treatment are not particularly limited. For example, the following conditions are preferably adopted as the heat treatment conditions: heat treatment temperature: 600°C to 1200°C, in an inert atmosphere (N2 atmosphere, Ar atmosphere). (2) Molding (press molding) The insulating coated soft magnetic metal powder 1 is placed in a mold and press molded at a molding pressure of 1.0 to 1.7 GPa to obtain a molded body. (3) Heat treatment (annealing) The obtained compact is heat treated (annealed) to obtain the powder magnetic core 10. Suitable heat treatment conditions include, for example, a heat treatment temperature of 600°C to 1200°C, a heating rate from 350°C to 600°C of 3°C / min or more, a holding time of 10 minutes to 120 minutes, and an inert atmosphere (N2 atmosphere, Ar atmosphere). The conditions of the heat treatment are appropriately changed depending on the types of soft magnetic metal powder and oxide used. EXAMPLES

[0036] The present invention will now be described more specifically with reference to examples.

[0037] 1. Preparation of powder core (1) Examples 1 to 19 The soft magnetic metal particles (raw powder) used were various particles having the types and average equivalent circular diameters shown in Table 1. In Table 1, each description represents the following particles. Fe: Pure iron particles Fe-Ni: Permalloy particles Fe-Si-Cr: Fe-3.5 mass% Si-1.5 mass% Cr particles produced by water atomization method Fe-Si-Al: Sendust particles Fe-Ni-Mo: Supermalloy particles Fe-Si: Fe-5.0 mass% Si particles produced by gas atomization method Fe-3.5Si: Fe-3.5 mass% Si particles produced by gas atomization method

[0038] Next, the soft magnetic metal particles were mixed with a suspension containing oxide particles of the type described in Table 1, a small amount of organic components, and a solvent, dried, and heat-treated. The concentration of oxide particles in the suspension was 0.1 to 2 mass% relative to the entire suspension. The amount of the suspension mixed with the soft magnetic metal particles was such that the total amount of oxide particles contained was 6 volume% relative to the soft magnetic metal particles. The heat treatment (first heat treatment) was performed under the conditions of a heat treatment temperature of 600°C to 1200°C in nitrogen. The heat treatment was performed for the purpose of removing organic components in the insulating layer and promoting the crystallization of the oxide. In this way, the insulating coated soft magnetic metal powders of Examples 1 to 19 were obtained. In addition, in Table 1, each description represents the following oxide particles. Al:Al2O3 particles Zr:ZrO2 particles Zr-Si:ZrO2-20 mass%SiO2 particles Al-Si:Al2O3-20 mass%SiO2 particles Zr-Al: ZrO2-10 mass% Al2O3 particles

[0039] The obtained insulating coated soft magnetic metal powder was placed in a mold and press molded at a molding pressure of 1.0 to 1.7 GPa to obtain a press molded body with a diameter of 10 mm. This molded body was heat treated (second heat treatment). The heat treatment was performed under the following conditions: heat treatment temperature: 600 to 1200°C, heating rate in the range of 350°C to 600°C: 3°C / min to 10°C / min, in nitrogen. In this way, the dust cores of Examples 1 to 19 were obtained. The crystallinity of the insulating layer was controlled by performing heat treatment at a higher temperature than in the past. Furthermore, the rate of temperature rise in a specified temperature range was increased to quickly obtain an insulating layer with high crystallinity. As a result, it was possible to shorten the temperature range required to form an insulating layer with high crystallinity, and it is presumed that this has suppressed the diffusion of specific elements that make up the insulating layer into the soft magnetic metal particles.

[0040] (2) Comparative Examples 1 and 2 The soft magnetic metal particles (raw powder) used were various particles having the types and average equivalent circular diameters shown in Table 1. Otherwise, the same procedures as in Examples 1 to 19 were carried out to obtain insulating coated soft magnetic metal powders and dust cores.

[0041] (3) Comparative Example 3 A suspension not containing oxide particles was used. Otherwise, the same procedures as in Examples 1 to 19 were carried out to obtain insulating coated soft magnetic metal powders and dust cores.

[0042] (4) Comparative Examples 4 and 5 The heat treatment temperature in the heat treatment (second heat treatment) was 600 to 1200° C., and the temperature increase rate in the range of 350 to 600° C. was 2.5° C. / min. Otherwise, the same procedures as in Examples 1 to 19 were carried out to obtain insulating coated soft magnetic metal powders and dust cores.

[0043] Table 1 shows the characteristics of the soft magnetic metal particles, the insulating layer, and the porosity of each of the examples and comparative examples. The "Crystal Orientation" column indicates the average number of regions measured for a particular grain, as measured by the method described in the embodiment. The column "Half width" indicates the half width of the strongest peak derived from the insulating layer, measured by the method described in the embodiment. The "Thickness of diffusion layer" column indicates the larger of the "thickness T1 of diffusion layer 5A" and the "thickness T2 of diffusion layer 5B" calculated by the method described in the embodiment. For Comparative Example 3, "-" is entered because no specific element was detected. Note that a graph of the Zr concentration and O concentration in the powder magnetic core of Example 2 is shown in FIG. The "Occupied Area" column indicates the percentage of the area occupied by the insulating layer, measured by the method described in the embodiment. The "total" column in the porosity indicates the ratio of the area occupied by pores to the area of ​​the field of view, measured by the method described in the embodiment. The "interface" column for porosity indicates the ratio of the area occupied by pores present between the soft magnetic metal particles and the insulating layer to the area of ​​the field of view, measured by the method described in the embodiment. The "Ratio" column for porosity indicates the percentage of the area occupied by pores between the soft magnetic metal particles and the insulating layer, when the total area occupied by pores, measured using the method described in the embodiment, is taken as 100%.

[0044] [Table 1]

[0045] 2. Loss Assessment Method Soft magnetic metal particles (median diameter D 50 The hysteresis loss, eddy current loss, and rate of variation in cycle testing of the powder cores of each of the examples and comparative examples were determined under the following conditions, with a powder core produced by press-molding only a powder core having a diameter of 40 μm and not conducting any heat treatment after molding (hereinafter referred to as a metal elemental powder core) being used as a reference. Number of turns: Primary: 20 turns, Secondary: 40 turns Applied magnetic field: 0.1T, Frequency: 30kHz~50kHz Cycle test: A heat cycle test was performed 300 times between temperatures of 25℃ and 200℃. The iron loss before and after the test was obtained, and the rate of change in the iron loss after the test was calculated based on the iron loss before the test.

[0046] The evaluation was as follows: Hysteresis Loss D: 95% or more of the hysteresis loss of the metal powder core C: 80% to 95% of the hysteresis loss of the metal powder core B: 70% to less than 80% of the hysteresis loss of the metal powder core A: Less than 70% of the hysteresis loss of a metal powder core "D" is defined as the case where the hysteresis loss is equal to or greater than that of a simple metal powder core.

[0047] eddy current loss D: 90% or more of the eddy current loss of a metal powder core C: 80% to less than 90% of the eddy current loss of a metal powder core B: 60% to less than 80% of the eddy current loss of the metal powder core A: Less than 60% of the eddy current loss of a metal powder core It should be noted that "D" is defined as a case in which the eddy current loss of the metal powder core is not clearly improved.

[0048] Cycle Test C: Iron loss fluctuation rate is 10% or more B: Iron loss fluctuation rate is 5% or more and less than 10% A: Iron loss fluctuation rate is less than 5%

[0049] 3. Evaluation results The evaluation results are shown in Table 1. Examples 1 to 19 satisfy the following requirements (a), (b), (c), and (d). Requirement (a): The soft magnetic metal particles have an average equivalent circular diameter of 10 μm to 100 μm. Requirement (b): The insulating layer contains an oxide of at least one specific element selected from the group consisting of Al, Zr, and Si. Requirement (c): The half-width of the strongest peak derived from the insulating layer as measured by XRD is 0.80° or less. Requirement (d): The thickness of the diffusion layer in which a specific element is diffused in the surface layer of a soft magnetic metal particle is 50 nm or less.

[0050] In contrast, Comparative Examples 1 to 5 do not satisfy the following requirements. Comparative Examples 1 and 2 do not satisfy the requirement (a). Comparative Example 3 does not satisfy the requirements (b) and (c). Comparative Examples 4 and 5 do not satisfy the requirement (d).

[0051] In Examples 1 to 19, the hysteresis loss and the overcurrent loss were suppressed in a well-balanced manner compared to Comparative Examples 1 to 5. Furthermore, in Examples 1 to 19, the performance degradation after the thermal cycle was small. Among Examples 1 to 19, Experimental Examples 5 to 19, which further satisfied the following requirement (e), had smaller hysteresis loss. Among Examples 1 to 19, Experimental Examples 10 to 19, which further satisfied the following requirement (f), had smaller hysteresis loss. Among Examples 1 to 19, Experimental Examples 13 to 19, which further satisfied the following requirement (g), had smaller eddy current loss. Among Examples 1 to 19, Experimental Examples 17 to 19, which further satisfied the following requirement (h), had smaller eddy current loss and exhibited less performance degradation after thermal cycling. Requirement (e): The average number of areas measured for a specific particle is 9 or less. Requirement (f): The area ratio of the insulating layer is between 4% and 9%. Requirement (g): The ratio of the area occupied by pores to the area of ​​the field of view is 5% or less, and when the total area occupied by pores is taken as 100%, the ratio of the area occupied by pores between the soft magnetic metal particles and the insulating layer is 20% or less. Requirement (h): The difference between the thermal expansion coefficient of the soft magnetic metal particles and the thermal expansion coefficient of the insulating layer is 3.0×10 -6 / K or less.

[0052] 4. Effects of the embodiment The dust core of this example had low hysteresis loss and low eddy current loss.

[0053] The present invention is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the claims of the present invention. [Industrial Applicability]

[0054] The dust core of the present invention is particularly suitable for use in motor cores, transformers, choke coils, noise absorbers, and the like. [Explanation of symbols]

[0055] 1...Insulating coated soft magnetic metal powder 2,2A,2B…Soft magnetic metal particles 3...Insulating layer 5A,5B…Diffusion layer 6,6A … Pore 10...Powder magnetic core

Claims

1. An insulating coated soft magnetic metal powder comprising soft magnetic metal particles having an average equivalent circular diameter of 10 μm to 100 μm and an insulating layer formed on the surface of the soft magnetic metal particles, the insulating layer contains an oxide of at least one of Al and Zr; the half-value width of the strongest peak derived from the insulating layer as measured by XRD is 0.80° or less; The insulating coated soft magnetic metal powder has a diffusion layer in which the element is diffused on the surface layer of the soft magnetic metal particle, the diffusion layer having a thickness of 50 nm or less.

2. 2. The insulated coated soft magnetic metal powder according to claim 1, wherein the specific particles are particles having an equivalent circle diameter of 50 μm to 100 μm among the soft magnetic metal particles, and when cross sections of 10 or more different specific particles are subjected to crystal orientation analysis and the number of regions separated by an orientation difference of 5° or more is measured for each of the specific particles, the average number of the regions measured for each of the specific particles is 9 or less.

3. A dust core comprising the insulating coated soft magnetic metal powder according to claim 1 or 2.

4. 4. The powder magnetic core according to claim 3, wherein when a cross section of the powder magnetic core is observed in a field of view of 500 μm × 500 μm, a ratio of an area occupied by the insulating layer to an area of ​​4% or more and 9% or less when an area of ​​the entire powder magnetic core is taken as 100%.

5. When a cross section of the powder magnetic core is observed in ten consecutive fields of view of 100 μm×100 μm, the ratio of an area occupied by pores to an area of ​​the fields of view is 5% or less, 5. The powder magnetic core according to claim 3, wherein a ratio of an area occupied by pores present between the soft magnetic metal particles and the insulating layer is 20% or less when an entire area occupied by the pores is taken as 100%.

Citation Information

Patent Citations

  • Ferromagnetic powder for dust core, dust core and its manufacture

    JP1998335128A

  • Method for producing metallic fine particle, and metallic fine particle

    JP2005120470A

  • Manufacturing method of dust core

    JP2009164401A

  • Insulator coating soft magnetic powder, dust core, magnetic element, electronic apparatus, and moving body

    JP2019192868A

  • Powder-compact magnetic core

    JP2020155674A